The first healed injury in a hyolith operculum - Fatka, Oldřich; Valent, Martin; Budil, Petr (Die Naturwissenschaften, 2023)
The Palaeozoic sediments of the Barrandian area are globally well-known as a classic example of rocks characterised by an abundant skeletal marine fauna, including well-preserved remains of hyoliths. Several tens specimens of malformed invertebrates such as trilobites, cephalopods and gastropods have been collected and documented from Cambrian to Devonian clastic sediments and carbonates in this area. However, no malformed hyolith specimen has yet been recorded. Hyoliths are Palaeozoic animals with small calcium carbonate shells composed of the conch (= oblong, conical and bilaterally symmetrical shell of diverse cross section and aperture at its wide end) and the operculum (= cap closing the conch aperture). Here we describe an operculum showing regeneration after non-lethal predatory attack in the Ordovician hyolith Elegantilites custos. This is the first record of regeneration in a hyolith operculum that has been repaired after a failed durophagous attack. Epibenthic/infaunal predatory echinoderms, such as ophiuroids, are considered as potential culprits.
Keywords: Invertebrates; Hyolitha; Fossils; Failed predation; zvířata; Prague Basin; bezobratlí; zkameněliny; Animals; Ordovician